Development and implementation of subject and intersubject curriculum and didactic packages and activation of motivation processes of students’ cognitive activity as parts of a didactic intensification of educational activity - Малихіна, Світлана Вікторівна (Pedagogy of Higher and Secondary Education, 2015)
Malykhina S. V. Development and implementation of subject and intersubject curriculum and didactic packages and activation of motivation processes of students’ cognitive activity as parts of a didactic intensification of educational activity. The article explains some minor didactic conditions of students’ educational activities didactic intensification. The ways of didactic intensification implementation, its didactic conditions as certain requirements to ensure its guaranteed performance have been determined.